AUTOMATING HORIZONTAL BORING AND MILLING MACHINE - R. Naqvi, S. A.; Mahmood, T.; Choudhry, M. A.; Hanif, A. (The Nucleus, 2012)
Aiming at the requirements of modification for many old import machine tools in industry, the schemes suited to the renovation are presented in this paper. A horizontal boring and milling machine (HBM) involved in machining of tank AlKhalid has been modified using Mitsubishi FX-1N and FX-2N PLC. The developed software is for control of all the functions of the said machine. These functions include power on/off oil pump, spindle rotation and machine movement in all axes. All the decisions required by the machine for actuation of instructions are based on the data acquired from the control panel, timers and limit switches. Also the developed software minimize the down time, safety of operator and error free actuation of instructions.